Extradigestive Manifestation of Helicobacter Pylori Infection in Children and Adolescents - Philip M Sherman; Frank YH Lin (Canadian Journal of Gastroenterology)
Helicobacter pylori infection fulfills each of Koch's postulates as a human pathogen causing chronic active gastritis. Disease consequences that develop in a subset of infected subjects include peptic ulcerations, gastric adenocarcinoma and mucosa-associated lymphoid tissue lymphoma. More recently, multiple publications have advocated a role for H pylori infection in causing a variety of extraintestinal manifestations. Many of these reports suffer from being case reports or case series without adequate controls. As a result, purported manifestations may simply be coincidental in nature. On the other hand, increasing evidence supports H pylori infection as a cause of sideropenic (refractory iron deficiency) anemia. Moderate evidence supports H pylori gastric infection as a cause of some cases of immune thrombocytopenic purpura due to molecular mimicry. Guidelines should be adjusted in accordance with advancing knowledge in the field.